Pengelolaan Data Penelitian pada Repositori Pengetahuan di Perpustakaan Khusus Lembaga Pemerintah Non Kementerian - Tupan Tupan; Mohamad Djaenudin (Media Pustakawan, 2020)
This study focuses on the analysis of research data management in the knowledge repository in a special library of non-ministerial government institutions consisting of LIPI, BPPT, BATAN, BAPETEN, LAPAN and BSN.The research was conducted using descriptive methods, namely by describing and interpreting a phenomenon that develops by using scientific procedures to actually answer the problem. Data collection was carried out through interviews and surveys of repository managers. The results showed that the LPNK Special Library of the Ministry of Research, Technology and Higher Education had mostly collected research data stored in the knowledge repository by means of direct input in the national scientific repository (RIN). Developing a knowledge repository in a special library is done because of the need to store data and research work in one place. The knowledge repository serves as a digital storage provider for long-term data storage and scientific work. The knowledge repository can make it easier for users to browse or reference data and the work of other researchers. The availability of knowledge repositories can also facilitate interdisciplinary learning and research. The obstacle in managing research data is that researchers have so far not paid enough attention, especially in terms of research data backup. There is a lack of trust from data owners to share their data because there is no legality, infrastructure and clear management. Libraries do not require researchers to store data in knowledge repositories and there is no government regulation that regulates inter-institutional research data management.